ANALYSIS OF THE EFFECT OF ESG ON THE FINANCIAL PERFORMANCE OF PUBLIC COMPANIES ON THE INDONESIA STOCK EXCHANGE 2018-2022 - Silvi Nur Rohma; Sari, Dewi Purnama; Paska, Yesica Apriliana; Amalia, Nabila Rizki (ANALISIS, 2026)
The purpose of this research is to examine how Environmental, Social, and Governance (ESG) disclosure affects business financial performance. This study examines financial performance using Return on Assets (ROA) data. Thomson Reuters provides ESG score data. The study population consists of companies listed on the Indonesia Stock Exchange with complete ESG data from 2018 to 2022. The sample was selected using a purposive sampling strategy, and hypothesis testing was conducted using multiple linear regression analysis. The final sample size for this study was 38 companies, based on the selection criteria. The findings indicate that ESG disclosure has a beneficial and significant impact on corporate financial performance. When considered individually, each ESG pillar (environmental, social, and governance) has a significant impact on ROA. This study suggests that promoting environmental responsibility, social responsibility, and effective corporate governance can improve financial performance. Furthermore, the study shows that ESG has a stronger impact on ROA in larger organizations